Rancang Bangun Turbin Angin Savonius Generator DC Dengan Tegangan 24 Volt Sebagai Penerangan Jalan Daerah Pesisir - Rifki Ardi Nawan; Muhammad Risyaf Raynaldi; Adi Winarno (SinarFe7, 2022)
Energy consumption is increasing day by day and is very focused on the use of fossil energy, or better known as fossil fuel, which is now decreasing in number and the price is certainly more expensive. On the other hand, there are various types of renewable energy available, abundant in number and of course very cheap and non-polluting, including water energy, solar energy, biomass energy, wind energy, and it is usually called renewable energy. be used as a priority to accompany or replace the use of fossil fuels. This energy research is carried out to avoid energy scarcity in the future. Through the development of energy conversion machines, renewable energy can be utilized optimally in Indonesia for energy needs to support human needs in the energy sector. Renewable energy that is very close to us, we even feel it every day is wind energy, and in coastal areas there is a lot of potential for wind to use wind energy. This potential can be developed through the use of windmills. One form of windmill that is easy to make is the Sovanius windmill. The advantage of this windmill is that it can make initial rotations with low wind gusts.